Managers’ Beliefs about Measures to Retain Senior Workforce - Mykletun, Reidar J.; Furunes, Trude; Solem, Per Erik (Nordic Journal of Working Life Studies, 2012)
This paper aims to describe and explain the beliefs of public sector managers regarding measures to promote active ageing within organizations and how these beliefs can relate to their own attitudes, age, gender, organizational roles, and structures. Data were collected by mailed questionnaires from 672 managers on operative and administrative levels in the Norwegian municipal and health sectors. It was found that managers believe in the usefulness of at least seven different measures, identified by factor analyses. Sum scores were calculated from the factors, and five of them showed sufficient reliability. Ranked according to their mean values, the factor-based sum scores were 1) reducing working hours, increasing the number of holidays, and offering flexible part-time schedules without a reduction in wages; 2) reducing workload and demands; 3) increasing wages, pensions, and bonuses; 4) increasing esteem, learning, and job enrichment for the senior workers; and 5) repositioning the workers to other, less demanding parts of the organization. In multiple regression analyses, these sum scores were found to be influenced mainly by the managers’ individual attributes, like age, gender, own retirement plans, beliefs, and attitudes. Organizational and structural factors seemed less important. The findings are discussed within three schools of thought: the ‘Human Relations Model,’ the ‘Market Model,’ and the ‘Age Management Model.’ A fourth ‘school,’ the ‘Laissez-faire Model,’ is indicated by the 26% of managers who claimed no responsibility for the age management issues.